Effects of plant harvest age and plant parts on phytochemical compounds of Andrographis paniculata (Burm. F.) Nees - Tajidin, Nor Elliza (2017)
Andrographis paniculata (Burm. F.) Nees (hempedu bumi) is harvested from the wild or cultivated area, causing variations in quality and consistency of the plant extracts and active compounds. Variations in its bioactive compounds, andrographolide (ANDRO), neoandrographolide (NAG), 14-deoxy-11, 12-didehydroandrographolide (DDAG), especially due to harvest age and plant parts used affect medicinal properties of the plant. The objective of this study was to determine optimum harvest age and suitable plant parts for quality and consistency of phytochemical compounds in A. paniculata. In Experiment 1, seedlings were raised in a nursery, field transplanted at 8 weeks after sowing (WAS), and harvested at 14, 16, 18, 20 and 22 WAS. Plant growth, phytochemical compounds, and heavy metal contaminations were determined. In Experiment 2, optimum harvest age of 19 WAS that produced highest bioactive compounds were selected for further phytochemical compound analysis in different plant parts (leaves, stems, and aerials) of young and mature development stages. In Experiment 3, verification in metabolites, bioactive compounds in young and mature leaves, and also young leaves harvested at 14 to 22 WAS were conducted using proton magnetic resonance (1H NMR) combined with multivariate analysis. The maximum increment rate in height and number of leaves and branches were at 16 and 22 WAS, respectively. Specific leaf area decreased by 41% as plant harvest age increased. Maximum ANDRO, NAG, and DDAG contents were obtained at 19, 18.5 and 18 WAS, respectively. Plant fresh and dry weights did not correlate with bioactive compounds. Total phenolic content increased by 17.6% from 14 to 19.06 WAS (36 to 42.36 mg GAE/100 g DW) and decreased by 3% until 22 WAS. Total flavonoid content showed a cubic relationship (r2 = 0.97) with harvest age. Antioxidant activities, except for reducing power, were highest at seed formation stage. The chlorophyll content started to increase by 47.7% from 14 (3.54 mg/g) to 20 (5.23 mg/g) WAS, remaining constant until seed formation. Heavy metal contents were below the permissible limits of WHO. In Experiment 2, the leaves had a highest extraction yield, followed by aerial parts and stems. ANDRO was 56.2% in young compared to mature plants. ANDRO of mature leaves (1.18 mg/g) and mature aerial parts (1.03 mg/g) were 87.1% and 62.7% higher, respectively, compared to mature stems (0.63 mg/g). The NAG content of mature stage was 2.9 times higher than young stage. Mature leaves have highest NAG compared to young aerial and young stems. DDAG in mature stems were lower than other plant parts. Total flavonoid content, hesperetin and DPPH free radical scavenging activity was highest at young stage while rutin, FRAP and reducing power were highest at a mature stage. No significant differences were recorded in contents of total phenolics, naringin, kaempferol, and glycosaponin, and scavenging activity of hydrogen peroxide in young and mature plants. Seven metabolites, ANDRO, NAG, DAG, glucose, sucrose, choline, and alanine, were identified. Principle component analysis (PCA) indicated clear discrimination between young and mature leaves. This discrimination was influenced by the presence of glucose, sucrose, NAG and choline in mature leaves compared to ANDRO and DAG in young leaves. Analysis using PC 1 and PC 2 of young leaves harvested from 14 to 22 WAS showed trajectory changes in metabolites. A loading plot confirmed differences in metabolic patterns of the groups. From regression analysis ANDRO, NAG and DAG were maximum at pre-flowering and early flowering stages while glucose and choline increased with harvest age. Thus, A. paniculata young leaves should be harvested at pre-flowering stage (19 WAS) to obtain maximum yield and phytochemical properties with minimal heavy metal contents.